Hypertoric manifolds of infinite topological type - Dancer, A (Elsevier, 2019)
We analyse properties of hypertoric manifolds of infinite topological type, including their topology and complex structures. We show that our manifolds have the homotopy type of an infinite union of compact toric varieties. We also discuss hypertoric analogues of the periodic Ooguri–Vafa spaces.